NEGOSIASI IDENTITAS PEREMPUAN PENGGEMAR SEPAK BOLA - Bayu Satwika, Jonathan; Dwiningtyas Sulistyani, Hapsari; Ratri Rahmiaji, Lintang (Interaksi Online, 2024)
Football communities are predominantly male and hegemonically masculine, often subjecting female fans to stereotypes and unpleasant treatment. Despite this, many women actively engage in football fandom and community activities. This research explores how women negotiate their identity while participating in these male-dominated spaces. Four informants from two football clubs were interviewed using dialogic narrative analysis based on Labov's narrative stages model. Identity negotiation, performance, and management theories were applied to understand their experiences The findings reveal that male dominance and masculine hegemony persist, making identity negotiation inevitable. However, growing gender equality discussions have led to greater acceptance of female fans. Today, female fans are more likely to be valued and integrated with male fans. The identity negotiation process varies, influenced by individual experiences. Some women choose to ignore or normalize the negative behaviors of male fans, while others perform certain behaviors to balance group expectations with their personal identity. These performances include maintaining a positive image with parents, actively engaging in fan activities, and mimicking typically masculine behaviors, like showing toughness. Family support or rejection also plays a crucial role in shaping women's continued involvement in football fandom.